Novel systemic therapies for the treatment of psoriasis. (2nd January 2016) - Tan, Ki-Wei; Griffiths, Christopher EM
Abstract : Introduction : The immunopathogenesis of psoriasis has led to the discovery and development of several promising treatment options for psoriasis, including those that target the IL-17 and IL-23 pathways as well as small molecules that act on intracellular signaling pathways including the Janus kinase inhibitor and phosphodiesterase-4 inhibitor. Studies have demonstrated efficacy although long-term risks are not fully known. This review looks at novel systemic therapies for psoriasis that have emerged recently. Areas covered : Systemic treatments for psoriasis that are in the late phase of development were reviewed, with the main focus on the efficacy and adverse effects of individual treatments. Expert opinion : The future of psoriasis treatment is likely to be based on clinical, genetic and immune biomarkers that will individualize treatment and may potentially optimize disease outcome.